The Scheduling Model Based on Precedents - S. Nesterenkov (Цифровая трансформация)
The paper presents an approach for university scheduling based on precedents. The model is based on the mathematical apparatus of the theory of graphs. The model uses the principles of finding and proof of the graph isomorphism. The process of finding of the graph isomorphism described in terms of relational algebra. Experimental studies showed expediency of this approach using in the preparation of the real schedule, as well as the possibility of reducing the dimension of the  NP-complete problem approximately 38.5%.